Extensive reading as a way to improve students' English ability in Shipbuilding Polytechnic - Lusiani Eni Puspandari (Jurnal Linguistik Terapan, 2015)
Reading is one of skills that must be mastered by people in understanding English. A good reading competence will influence the people's ability in English. From the reality that many students feel difficult in understanding some meaning in English, another way is found out in order to improve the students' English proficiency by using and extensive reading. Extensive reading involves students in reading large quantities of books at the level appropriate for them; only one to two words per page should be unknown to a reader. The primary goal of Extensive reading is reading in order to gain information and to enjoy texts. Extensive reading (ER) has been seen as an indispensable means of developing learners’ reading ability and enriching their knowledge of the language and the world. Considering that the students of Shipbuilding Polytechnic has limited time in learning English, the Extensive Reading program is one solution for them in improving their English proficiency.